Perspektivy farmakologického a klinického prínosu aktivátorů sirtuinu 1 pri oxidativním poskození - Kutinová, Canová Nikolina; Gaier, Norbert; Farghali, Hassan (Casopis lekaru ceskych, 2012)
Sirtuins, named after their homology to the Saccharomyces cerevisiae Silent Information Regulator Two, constitute a family of highly conserved nicotinamide adenine dinucleotide-dependent enzymes that deacetylate histones and residues of acetylated lysine. The main aim of this article is to put forward the pharmacological importance of major sirtuin 1 activators of natural or synthetic origin tested in last years in cases of oxidative tissue damage. The related bioactivity of these activators as "leading" compounds in the search for new drugs and remedies is also described. With the recent development of our knowledge on the cross talks between sirtuin 1 and its modulators (e.g. resveratrol), pharmacological and clinical research on this topic is getting a new horizon.
Keywords: Oxidative Stress; Sirtuin 1; antioxidancia; oxidační stres; Humans; sirtuin 1; lidé; Antioxidants